Plan estratégico de marketing para mejorar el posicionamiento de la Empresa Avícola Yema de Oro S.R.L. 2011. - Diaz Chacón, Hebert Esteban (2012)
This research aimed to develop a strategic marketing plan to improve the positioning of the Poultry Company "Golden Yolk SRL" in the city of Trujillo, with this end we used a type of research is not experimental, cross a 1 single box. There were 25 questions which were put at random for the survey of retail outlets in the town of Trujillo, to set your preferences and recall of that poultry company. In addition development were used as data collection techniques: observations, interviews, surveys. One result obtained was that the poultry company "Golden Yolk SRL" has no recollection of most of the outlets in the town of Trujillo. It was noted that the results is the need to develop a strategic marketing plan for the company to improve its position in the city of Trujillo. As a result of the research is concluded: strategic marketing plan for the poultry company "Golden Yolk SRL" will improve its position in the city of Trujillo, also allow you to survive in this competitive industry, because the battle being waged in the minds of consumers.*